Estrategia psicopedagógica basada en el programa Decedario para mejorar la memoria de trabajo de una estudiante de séptimo grado con discapacidad intelectual leve de la unidad educativa fiscomisional Educare, 2023 - Agila Saavedra, Julia Cecibel (2023)
The objective of this Curricular Integration Work was to apply the psychopedagogical strategy based on the Decedario program to improve the working memory of a student with mild intellectual disability from the Educare fiscomisional educational unit, 2023. The qualitative approach, descriptive type, was used. cross-sectional, atypical case study method. As techniques and instruments, the psychopedagogical sheet, semi-structured interview, checklist, neuropsychological battery of executive functions and BANFE-2 frontal lobes were applied. The results found at the discretion of the teacher through the semi-structured interview indicate that the student presents multiple problems, including the deficiency of her working memory since she does not retain the information due to the mild intellectual disability she presents and her level of learning is very low compared to students of his age; Through the self-directed pointing, visuospatial working memory and alphabetical ordering of words tests, belonging to the neuropsychological battery of executive functions and frontal lobes, BANFE-2 is classified according to its classification as a severe type of alteration. Faced with this, the psycho-pedagogical strategy “Working on memory without diversity” was designed, adapted to the needs of the student, composed of three activities as a welcome dynamic or setting; central activity with the use of the “Decedario” program and reinforcement activities, concluding according to the checklist that the student's achievements after the application of the psychopedagogical strategy were notable.